A Systematic Literature Review on Technostress in Post-COVID-19 Education: Psychological Stressor, Antecedents, Mitigation Strategies, and the Role of Counseling - Vermila, Ayu; Kurniawati, Farida (Universitas Negeri Padang, 2025)
This systematic literature review (SLR) explores technostress among educators in post-COVID-19 education. While technostress—stress caused by technology use—has been extensively studied in non-educational settings, its impact on educators remains underexamined, particularly as the pandemic accelerated digital adoption in teaching. This review addresses this gap by analysing the key stressors associated with technology, their underlying causes, their effects on educators, and potential mitigation strategies, including the role of counselling. We used the PRISMA guidelines to search six academic databases (Emerald Insight, ProQuest, Taylor & Francis, SAGE, ScienceDirect, and Scopus) for peer-reviewed studies published between 2020 and 2025 that look specifically at tech-related stress among teachers. The search initially yielded 1,142 articles, with 23 meeting the inclusion criteria for in-depth analysis. The findings reveal that excessive digital workloads, the complexity of new technological tools, work-life imbalance, and inadequate institutional support are primary contributors to technostress. These challenges are further exacerbated by limited training and resources. Additionally, individual factors such as digital competence, self-efficacy, and Technological Pedagogical Content Knowledge (TPACK) play a significant role in determining educators’ ability to cope with technology-related stressors. This review provides valuable insights into the challenges of technostress and outlines strategies for intervention. The findings offer practical recommendations for educational institutions, policymakers, and counsellors to create more sustainable and supportive digital learning environments.